Deduction level of undergraduate students' imagination in solving geometrical problem. (February 2020) - Mahfut, M; Sunardi,; Yudianto, E; Purnomo, R C; Firmansyah, F F
Abstract: This research aims to know the imagination process on Mathematics' undergraduate students who had deduction level in solving Geometrics' problem. This research is qualitative which the subjects in the research were 2 students that one female and one male. To know the imagination process, subjects were asked to solve two Geometrics' problems. Analysis was done to determine the indicators of imagination that appeared for each subjects. To improve the data accuration, the researcher used triangulated data method for the data collection method, such as observation, students' worksheet, and interview. The result showed that there were differencies that appeared for each subjects.